Pola Nama Desa di Kabupaten Ponorogo pada Era Adipati Raden Batoro Katong (Sebuah Tinjauan Etnolinguistik) - Alip Sugianto (Jurnal Sosial Humaniora, 2017)
This paper expplains that the Pattern Name of villages in Ponorogo at periodof Duke Raden Katong Batoro has some morphological word formations andmeanings. For the method, this research used literature and historicalanalysis. Research shows that names of the village in Ponorogo relate toBatoro Katong. From the historical point of view, names of the villages camefrom the names of People Punggawa Raden Batoro Katong who have lived inand founded Ponorogo. This was intended for the remembrance of RadenKatong Batoro’s struggle, the founding father of Ponorogo.